Enhancing water-based mud properties with sodium lignosulfonate polymer and silicon dioxide nanoparticles: A study on interfacial tension and aging behavior - Norida, Ridzuan; Ling, Chung King; Ahmad Syahmi, Tajarazhar (Springer Singapore, 2024)
Water-based mud (WBM) is extensively utilized as a drilling fluid because of its cost-effectiveness and eco-friendly nature. This study aims to investigate the effect of adding sodium lignosulfonate (SLS) polymer on the interfacial tension (IFT) between polymer solution and crude oil. Silicon dioxide (SiO2) nanoparticles and SLS polymer were used at different concentrations to evaluate their impact on WBM properties and aging behavior. Various tests were performed to evaluate the mud density, pH, rheological properties, fluid flow behavior, filtration properties, and surface tension of the WBM. From the results, the addition of 3.2 wt% SLS polymer resulted in the lowest IFT. The apparent viscosity (AV) and plastic viscosity (PV) increased with nanoparticle concentration but decreased with polymer addition. The yield point and gel strength decreased and increased with the addition of nanoparticles and polymer, respectively. A concentration of 1.6 g of SLS polymer was found to be optimal as it lowered viscosity. Nanoparticles increased filtration properties, while polymers decreased filtration properties as their concentration increased. The optimal concentration of nanoparticles in WBM was found to be 0.8 g. In conclusion, nanoparticles increased rheological and filtration properties, while the polymer decreased these properties.